A cost‐effectiveness analysis of lusutrombopag for thrombocytopenia in patients with chronic liver disease in Japan. Issue 8 (26th June 2021) - Miki, Norikane; Inoue, Sachie; Shibahara, Hidetoshi; Kurazono, Kenji; Perard, Rodolphe; Tateishi, Ryosuke
ABSTRACT: Background and Aim: Thrombocytopenia is a frequent hematological condition in chronic liver disease (CLD) patients increasing the risk of bleeding in patients undergoing invasive procedures. Without an alternative, clinical guidelines recommended the use of platelet transfusion (PT) prior to procedure to prevent this bleeding risk. Lusutrombopag (LUSU), an orally active, small‐molecule thrombopoietin receptor agonist, was developed as an alternative to PT. The objective of this study was to evaluate a cost‐effectiveness of LUSU as a potential alternative to PT in Japan. Methods: A cost‐effectiveness analysis of LUSU relative to PT was conducted by a simulation model consisting of a decision tree combined to Markov model. Quality‐adjusted life years (QALYs) were used as an indicator of efficacy, and the analysis was conducted from the Japanese public healthcare payer's perspective. The time horizon of the analysis was 50 years (a lifetime) and the discount rate was set at 2%. Results: LUSU gained 6.1803 QALYs with an expected lifetime costs of 2 380 219 JPY compared to PT with 6.1712 QALYs gained and expected lifetime costs of 2 382 908 JPY. Thus, LUSU was deemed dominant compared with PT. Based on probabilistic analyses, the chance of LUSU being dominant and the incremental cost‐effectiveness ratio being below 5 million JPY/QALY was estimated at 51.8% and 78.3%, respectively, demonstrating the robustness of the results. Conclusions: LUSU was evaluated as an efficacious and cost‐saving treatment option for Japanese CLD patients with thrombocytopenia who required a planned invasive procedure compared with PT and economically should be considered as an alternative treatment. Abstract : Thrombocytopenia is a frequent hematological condition in chronic liver disease (CLD) patients increasing the risk of bleeding in patients undergoing invasive procedures, and the use of platelet transfusion (PT) was recommended prior to procedure to prevent this bleeding risk. This study evaluated the cost‐effectiveness of lusutrombopag (LUSU) as a potential alternative to PT in Japan by using a simulation model consisting of a decision tree combined to Markov model. Compared with PT, LUSU was found to be an efficacious and cost‐saving treatment option for Japanese CLD patients with thrombocytopenia who required a planned invasive procedure.